Analisis Karakteristik Biomassa Cangkang Kelapa Dan Kulit Mete Melalui Proses Torefaksi - Nurudin, La Ode; Mangalla, Lukas Kano; Barata, La Ode Ahmad (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2022)
In the face of the depletion of fossil fuels, alternative fuels such as biomass are needed. However, biomass has a fairly low calorific value and several other disadvantages compared to petroleum. Therefore, a new breakthrough is needed to correct these weaknesses, one of which is the Torrefaction process. The purpose of this study was to determine the effect of torrefaction of coconut shell and cashew shell biomass on the physical and chemical properties of the material. This research was conducted using coconut shells and cashew shells. The results of this study indicate that the calorific value of coconut shells and cashew shells after torrefaction is 5115,297-5147,021 cal/gr. The water content in coconut shells is 2.718% and the value of water content in cashew shells is 2.397%, the ash content of coconut shells is 6.853% and the value of cashew shell ash content is 6.600%, the value of volatile levels of coconut shells is 14.885% and the value of volatile levels of cashew shells of 14.557% and the value of fixed carbon content of coconut shell is 75.574% and the value of fixed carbon content of cashew shell is 76.447%. Keywords : Biomass, coconut shell, cashewnut shell, torrefaction